Typology of social media followers - Ramadan, Zahy (2018)
Purpose Luxury brands tend to be hesitant in adopting social media. This matter has created an imminent need to understand the different types of online luxury followers so as to help luxury brands communicate effectively with their consumers, while maintaining the “luxe” image and experience. Accordingly, the purpose of this paper is to provide luxury brands with a deeper understanding of their online audience and the strategies needed to engage with them through the different social media platforms. Design/methodology/approach A qualitative approach was utilized in which 24 in-depth interviews were conducted with Lebanese followers of an online luxury brand’s social media pages. Findings The study identifies the presence of six main categories of online luxury followers: pragmatists, bystanders, trend hunters, image seekers, passionate owners, and prime consumers. Each group has a specific engagement and propensity to buy levels. Research limitations/implications Understanding the different segments of luxury brand followers provides a framework for marketing managers that allows them to correctly target their marketing and communication strategies in order to maximize consumer engagement and purchasing behaviors. Originality/value A significant gap exists in the extant literature which offers no understanding of the different luxury brand followers and their different characteristics. This study is the first to offer an exploratory typology of the various luxury brand followers on social media platforms.